Kajian Faktor Risiko Pelecehan Seksual Anak di Indonesia Tahun 2020 - Maria Regelinda Fallo; Cucu Sumarni (Politeknik Statistika STIS, 2022)
Cases of sexual abuse that afflict children in Indonesia continue to increase from year to year. This increase in cases needs to be prevented so that the impacts experienced by victims such as physical, psychological, material and economic and social impacts can be reduced. Therefore, this study aims to examine the risk factors that cause a child to become a victim of sexual abuse in Indonesia in 2020. The data used is raw data from the 2020 National Socio- Economic Survey conducted by the Central Statistics Agency where the data is known to be a rare event so that it is processed. using Firth logistic regression method. The results showed that with a significance level of 10% the more prosperous the family, female children, children with at least one disorder from all types of disorders, children who have used the internet in the last three months, and children whose heads of household have low education, it will increase the risk of a child becoming a victim of sexual abuse.